Microwave-assisted rapid MAX phase etching and delamination: A paradigm shift in MXene synthesis - Numan, A. (Elsevier Ltd, 2022)
This work describes a novel and rapid strategy to produce delaminated MXene sheets from the MAX phase. The current method uses a novel microwave-assisted hydrothermal method to etch aluminium (Al) from the MAX phase (as well as delaminate) within 2 h of processing which has remarkably reduced time from up to 48 h to 30 min and temperature from 180 to 40 Â°C. A range of characterizations was carried out to evaluate the properties of the MXene. The X-ray photoelectron spectroscopy and X-ray diffraction patterns exhibited the spectra typical of Ti3C2Tx extracted from Ti3AlC2 after rapid etching of Al. These results were complemented by scanning and transmission electron microscopies, UVâvisible absorption spectrum, and BET absorption-desorption curves. The results depicted the formation of high-quality MXene with negligible Al traces, which confirms the efficacy of the current method. This work not only establishes a comprehensive methodology for rapidly synthesizing high-quality MXene in bulk quantities but also opens up new avenues for its commercial applications. Â© 2022 Elsevier B.V.